ANALISIS ISI KRITIK POLITIK DALAM FILM DOKUMENTER THE ENDGAME - Achmad Herman; Nurul Fahri; Muhammad Wahid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This study aims to determine political criticism and the frequency of its appearance contained in the documentary film The EndGame. This research uses quantitative research on the basis of content analysis methods, sampling using a multistage random sampling technique, so that all scenes of the documentary film The EndGame that aired on the Watchdoc Documentary YouTube channel are used as research samples. The data collection technique uses data documentation techniques based on predetermined political criticism categorizations. Research samples were collected through coding sheets and data were analyzed using frequency distribution tables. The results of this study show that the documentary film The EndGame contains five political criticisms based on existing political problems, namely criticism related to state problems, power problems, decision making problems, general policy problems, and allocation problems. Meanwhile, the frequency of messages of political criticism found by researchers, namely the frequency of political issues that were criticized the highest, was a matter of power with a percentage of 60%, while the frequency of political issues that was criticized the lowest was a problem of allocation with a percentage of 3.64%.